2017
DOI: 10.1105/tpc.17.00612
|View full text |Cite
|
Sign up to set email alerts
|

ZEITLUPE Contributes to a Thermoresponsive Protein Quality Control System in Arabidopsis

Abstract: Cellular proteins undergo denaturation and oxidative damage under heat stress, forming insoluble aggregates that are toxic to cells. Plants possess versatile mechanisms to deal with insoluble protein aggregates. Denatured proteins are either renatured to their native conformations or removed from cellular compartments; these processes are often referred to as protein quality control. Heat shock proteins (HSPs) act as molecular chaperones that assist in the renaturation-degradation process. However, how protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Multiple studies have shown that the ability to clean up unfolded proteins corresponds to the ability of plants to survive exposure to extreme HT. For example, plants deficient in the expression of proteasome subunits (Li et al ), E3 ligases, and autophagy‐related genes (Zhou et al , ; Liu et al ; Gil et al ) are susceptible to HS. Moreover, transgenic plants overexpressing genes encoding either ubiquitin (Tian et al ) or ubiquitin E3 ligases (Lim et al ; Liu et al ; Liu et al ) exhibit enhanced basal and/or acquired heat tolerance.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Multiple studies have shown that the ability to clean up unfolded proteins corresponds to the ability of plants to survive exposure to extreme HT. For example, plants deficient in the expression of proteasome subunits (Li et al ), E3 ligases, and autophagy‐related genes (Zhou et al , ; Liu et al ; Gil et al ) are susceptible to HS. Moreover, transgenic plants overexpressing genes encoding either ubiquitin (Tian et al ) or ubiquitin E3 ligases (Lim et al ; Liu et al ; Liu et al ) exhibit enhanced basal and/or acquired heat tolerance.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Such disruption of metabolism additionally perturbs hormone biosynthesis and signalling, alters calcium signalling and induces the accumulation of metabolic intermediaries that can subsequently be transported from the mitochondria or chloroplasts to the nucleus (Chan et al ., ; Mullineaux et al ., ). With regard to circadian rhythmicity, high temperatures are sufficient to slow the circadian oscillator, and the circadian system is also delayed by osmotic stress (Gil et al ., ; Litthauer et al ., ). As with many stress responses, the question now facing the field is whether the clock is slowed under these environmental conditions as part of a generalized reaction to cellular damage, or whether specific retrograde signals delay circadian progression as part of an adaptive response.…”
Section: Retrograde Signals Contribute To Circadian Timingmentioning
confidence: 99%
“…These experiments were performed at 23°C, so clearly HSP90 is critical for proper maturation of ZTL outside of a possible role in heat responses, but this does not preclude a role for ZTL in heat stress responses through its interaction with HSP90. Gil et al (2017) now provide evidence that ZTL is an important player in thermotolerance.…”
mentioning
confidence: 99%
“…Among them, HSP90 ensures proper folding of the auxin receptor, disease resistance proteins, and the F-box protein ZEITLUPE (ZTL), a central component of the circadian system in Arabidopsis thaliana. New findings by Gil et al (2017) add a circadian dimension to plant responses to heat stress and show that ZTL mediates polyubiquitination of aggregated proteins, marking them for degradation by the 26S proteasome.…”
mentioning
confidence: 99%
See 1 more Smart Citation